A Study of the Influence of Religious and Nationalist-Based Political Parties in the Compilation of Legal Products Based on Legal Regulations - Suwandi, Dedy (Journal of Ecohumanism, 2024)
The ideology of political parties is divided into four categories: parties with Islamic ideology, secular nationalist ideology, religious nationalist ideology, and parties with Christian ideology. The regeneration process will bring out prospective leaders who have been tested in carrying out organisational work or society, and then the emerging decisions will be directed at achieving the goals of the country. These party cadres make a reflection of political parties related to ideology, which is expected to make policies in accordance with ideology, through being regional leaders. The research method used is sociological juridical with a qualitative descriptive analysis approach to obtain the answers to the problems studied, supported by secondary data and other data. When referring to the party principles owned by each political party, in general, political parties are based on three ideologies: Islam, Nationalism and Democratic Socialism. Political parties have an obligation to be able to build their own capacity; therefore, they have sufficient capability to fulfill what has been mandated by law. The fading of ideology has weakened the ties between political parties and their members, which in turn has resulted in the weakness of organisational networks. This condition leads the political parties to face an extreme dilemma. The way to collect party funds is by making policies that benefit certain parties. However, with transactional politics, the policies taken are not pro-people. The importance of the party's stand in policymaking is marked by their close relationship with elected and appointed political officials. For this reason, the party can see its role and influence in public policy using organisational theory. This fact shows that political parties are a more powerful element in the policy-making process than they should be.